Analysis of Crossref Reports in Order to Improve the Quality of Metadata of Scientific Publications - Ермаков, А.В. (Научный сервис в сети Интернет, 2021)
Issues related to improving the quality of metadata of scientific publications placed in the Crossref bibliographic database are considered. All information contained in metadata obtained from publishers of scientific publications is analyzed by Crossref and displayed in various reports. Analysis of these reports gives publishers an idea of the completeness and correctness of the bibliographic data presented. The quality of metadata directly or indirectly affects the number of views and links to a publication, respectively, on the ratings of scientific publications, authors and organizations.
Keywords: metadata of publications; Crossref reports; citations; ratings of scientific publications